Development Of Tourism Destinations And Visitor Participation Through The Empowerment Of The Thematic Village "Elo Pukek": Pengembangan Destinasi Wisata Dan Partisipasi Pengunjung Melalui Pemberdayaan Desa Tematik "Elo Pukek" - Amril, Imti; Anisa; Idir Tamsil (Journal of Community Service and Application of Science, 2024)
Thematic Village is one of the innovations of the Padang City Government to overcome problems in meeting basic needs, especially improving the quality of the environment, infrastructure and basic settlements. We chose the Thematic Village because we want to provide new innovations to develop tourist attractions to make them more advanced and much sought after by the community. Fishermen carry out the "Elo Pukek" activity or pulling trawls (nets) together on Padang Beach. The local government will develop the "Elo Pukek" tradition as one of the tourist attractions in Padang City to increase tourist visits and the fishing economy